2015
DOI: 10.15446/rfnam.v68n2.50982
|View full text |Cite
|
Sign up to set email alerts
|

A coating of chitosan and propolis extract for the postharvest treatment of papaya (Carica papaya L. cv. Hawaiiana)

Abstract: Propolis is a natural antimicrobial that can be used as a bioadditive in coatings to control fruit quality losses. The effect of two coatings was evaluated, a control (chitosan, 1%) and a treatment (chitosan, 1%; containing propolisethanolic extract, 5%), on the microbiological and physicochemical properties of papaya fruits. The chemical profile of the propolis revealed the presence of fatty acids and their esters, carbohydrates, diterpenic acids, and pentacyclic triterpenes. The fruits covered with the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 38 publications
2
23
0
5
Order By: Relevance
“…The survival rate also increased with propolis application. This antifungal effect of seed coatings based on propolis extracts has been already demonstrated for the postharvest treatment of papaya [45] and chilli [58] during storage. In vitro experiments demonstrated that the binary combination of chitosan and propolis was an efficient combination to deal with F. circinatum [14], Diplodia seriata [37], and Hemileia vastatrix [59].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The survival rate also increased with propolis application. This antifungal effect of seed coatings based on propolis extracts has been already demonstrated for the postharvest treatment of papaya [45] and chilli [58] during storage. In vitro experiments demonstrated that the binary combination of chitosan and propolis was an efficient combination to deal with F. circinatum [14], Diplodia seriata [37], and Hemileia vastatrix [59].…”
Section: Discussionsupporting
confidence: 58%
“…Propolis ethanolic extract (PEE) composites were prepared by introducing the finely grinded resin into a hydroalcoholic solution (7:3 v/v). After stirring for 72 h at room temperature, the insoluble particles were filtered [45].…”
Section: Preparation Of the Seed Coating Solutionsmentioning
confidence: 99%
“…This remarkable combination makes it an excellent candidate for preserving different foods. Successful experiments have been performed for utilization of propolis extracts in the preservation of numerous products: fruit juices [62][63][64][65], fruits [68][69][70][71][72][73][74][75][76][77], vegetables [78][79][80][81][82][83][84][85], eggs [86][87][88][89][90][91], meat and fish products [92][93][94][95][96][97][98][99][100] (Table 2). This field of application of propolis is rapidly growing, as indicated by the growing number of publications.…”
Section: New Fields Of Propolis Applicationmentioning
confidence: 99%
“…Hawaiiana) Ethanol extract Llanta Azul apiary, Zaragoza (Antioquia -Colombia) [77] Vegetables Rice (Oryza sativa, var. hinohikari) Absolute ethanol, methylene chloride and hexane extracts Brazilian green propolis [78] Carrot (minimally processed) 25% Water and alcohol extracts Brazilian green propolis [79] Lettuce Ethanol extract Bragança, Portugal [80] Cucumber 70% Ethanol extracts Pato Branco (PR), Brazil [81] Beans, carrots against white rot disease Alcohol extract Iraq [82] Mixed vegetables for soup Propolis extract Argentina [83] Celery, leek and butternut squash (minimally processed) Ethanolic extract; standardized to 10% propolis extract Mendoza province, Argentina [84] Chilli (Capsicum annuum L.) Ethanol extract Brazilian green propolis [85] Eggs Eggs quality during storage 70% Ethanol extract Hatay province, Turkey [86,87] Japanese quail eggs 70% Ethanol extract Hatay province, Turkey [88][89][90] Hens eggs Ethanol extract Parana state, Brazil, [91] Meat products Fresh oriental sausage 95% Ethanol extract Cairo, Egypt [92] Sausages 96% Ethanol extract Boyacá, Colombia [93] Fermented meat sausage "Alheira" 95 % ethanol Vila Franca, Viana do Castelo, Portugal [94] Beef patties Commercial ethanol extracts Sonora, Mexico, poplar type [95] Poultry meat product-cured cooked ham 96% Ethanol extract Slovakia [96] Fish products Nile tilapia (Oreochromis niloticus) fillets, frozen storage Water extract Egypt [97] Cachama fish (Piaractus brachypomus) fillets (refrigeration) 96% Ethanol extract Boyacá, Colombia [98] Fresh fish burgers 70% Ethanol extract La California, LI, Italy [99] Fresh shibuta (Barbus grypus) fillets Water extract Fanus Natural Company, Trabzon, Turkey [100] Others Milk protein concentrate (diary beverages) 94 % Ethanol extract Water extract Canada [101] Food packaging Chitosan-propolis coated polypropylene films 80% Ethanol extract Konya region, Turkey.…”
Section: 3mentioning
confidence: 99%
“…The quality of fish products was improved by adding propolis with the level up to 0.6% as well as the shelf-life of frozen stored of such products (Hassanin & El-Daly, 2013). Propolis extract was used as edible coating for papaya fruits and exhibited a huge microbial effects without adverse effects on the physicochemical properties of the fruits (Barrera et al, 2015). The propolis hydroalcoholic extract was effective coating and reduce the weight loss in orange fruits up to eighteen days storage (Passos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%